Student’s Writing Skills in Journalistic Texts as Basis for Developing E-Journalism Instructional Material - Nepomuceno, Irene; Mangindra, Anesa (International Journal of Arts, Sciences and Education, 2025)
The objective of this study is to determine the level of proficiency of Grade 8 students in writing journalistic works and to develop an e-journalism instructional material. The study was conducted at Esperanza National High School during the Third Quarter of the 2024-2025 academic year. The participants consisted of thirty (30) students selected through random sampling, and the study followed a Research and Development design. Each student was given three sets of writing tasks: news writing, radio documentary, and social campaign. These tasks were assessed based on technical aspects, content, and ethics for news writing and radio documentaries, and on technical aspects, content, and persuasiveness for social campaign writing. Based on the results, it was found that students demonstrated a high level of proficiency in news writing and radio documentaries, while their proficiency level in social campaign writing was moderate. In response, an e-journalism instructional material was developed to serve as a learning aid and guide for students in writing journalistic works. The e-journalism instructional material underwent validation and acceptance evaluation by teachers and students to determine its effectiveness based on survey results. The findings revealed that the developed instructional material received a high validation rating from expert teachers, indicating that its content is sufficient and appropriate for instructional use. Moreover, both teachers and students strongly supported the developed instructional material, signifying their agreement on its effectiveness and design. The study also showed no significant difference in the level of acceptance between teachers and students regarding the e-journalism instructional material. Therefore, the e-journalism material received equal recognition and acceptance from both teachers and students, demonstrating its potential as a valuable teaching tool.